FACTORS ASSOCIATED WITH THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN - Isra Wati; Rianti; Rasma; Murlan; La Ode Liaumin Azim (STIKes Budi Luhur Cimahi, 2025)
Anemia in pregnant women is a public health problem that has a significant impact on the mother and fetus. Anemia can increase the risk of premature birth, low birth weight, and maternal and infant mortality. In the working area of Puskesmas Wonggeduku Barat, the prevalence of anemia in pregnant women is still relatively high (25.6%) so it is necessary to conduct research to find out the risk factors more specifically. This study aims to determine the risk factors for Fe tablet consumption compliance, knowledge and diet with the incidence of anemia in pregnant women in the working area of Puskesmas Wonggeduku Barat. This type of research is observational analytic with case control study design. The population in this study consisted of a case population of 39 people and a control population of 39 people, with the total sample size being the number of case populations plus the number of control populations using a 1:1 ratio with matching gestational age, namely trimester I, II, and III so that the total sample size was 78 people. The results of the Odds Ratio test showed that compliance with Fe tablet consumption obtained an OR value of 1.758, knowledge obtained an OR value of 1.777 and diet obtained an OR value of 1.657. Because OR> 1, compliance with Fe tablet consumption, knowledge and diet are risk factors for the incidence of anemia in pregnant women in the working area of Wonggeduku Barat Health Center. Keywords: Anemia, Pregnancy, Fe tablets, Knowledge, Dietary habit